Preconcentration and Separation of Metal Ions Using Chelating Adsorbents Based on Naphthalene - Sharma, A.; Khiwani, D.; Bhojak, N.; P. Soni, K. (Asian Journal of Chemistry, 2016)
N-(2'-Pyridyl)-2-hydroxybenzamide (NPHB) supported on naphthalene has been used for the preconcentration and separation of cobalt and nickel ions. Further, a simple, convenient and rapid spectrophotometric method has been developed for the estimation of these ions. Co(II) and Ni(II) can be quantitatively determined using this adsorbent in a column in the pH range of 5.0 to 6.5 and 6.0 to 7.0 respectively with a flow rate of 2 mL min-1. Metal ions were detected spectrophotometrically at a wavelength of 434 nm for Co(II) and 455 nm for Ni(II). Beer’s law is obeyed up to 15 mg L-1 for Co(II) and 17 mg L-1 for Ni(Il) using this method with a sensitivity of 0.037 μg/cm2 for Co(II) and 0.030 for Ni(II). The concentration of metal ions has also been determined by means of atomic absorption spectrometry.